If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 43 = 4 + -3w Solving 43 = 4 + -3w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '3w' to each side of the equation. 43 + 3w = 4 + -3w + 3w Combine like terms: -3w + 3w = 0 43 + 3w = 4 + 0 43 + 3w = 4 Add '-43' to each side of the equation. 43 + -43 + 3w = 4 + -43 Combine like terms: 43 + -43 = 0 0 + 3w = 4 + -43 3w = 4 + -43 Combine like terms: 4 + -43 = -39 3w = -39 Divide each side by '3'. w = -13 Simplifying w = -13
| 22-6x=11-5x | | 3x^2y+4xy^2+y^3=0 | | 5x+20-8=x+32 | | 5p-12=8p+4 | | 2(3u+7)=-4(3-3u) | | 8y+4-2=22 | | 1460=250+24x | | (v+p)(v+p)-9=0 | | -6(w+3)+7=-35 | | 12+x+2+x+2= | | 3/5(35b+20)-2b=2/3(12b+21)+3 | | 9-5g=12-(6g+7) | | 12+58-8=12x-10 | | 8x+3-2(4x)= | | 7s-3.9s=6.2 | | 4x+3-6x=1-x | | 1/2(2x+12)+4=2x-1 | | =-(-w+6) | | 5(2-3w)+2w=23 | | 0=12x-48 | | -12w^2+w^3+36w=0 | | -5(w+4)+8=-32 | | 3(2x-1)=5x-2(2x-6) | | 2/3(d+3)=4 | | n+28=41 | | -.6+(-4x)=-1.4 | | 8x+8=50+2x | | 5j-5-3j=7 | | (x-3)=(x-2) | | -t+9=25 | | 7(2x+3)-5=2(4x+3)+3(x+1) | | -4=19+x |